Regulation of the Actin Cytoskeleton-Linked Ca2+ Signaling by Intracellular pH in Fertilized Eggs of Sea Urchin - Nunzia Limatola; Jong Tai Chun; Luigia Santella (Cells, 2022)
In sea urchin, the immediate contact of the acrosome-reacted sperm with the egg surface triggers a series of structural and ionic changes in the egg cortex. Within one minute after sperm fuses with the egg plasma membrane, the cell membrane potential changes with the concurrent increases in intracellular Ca2+ levels. The consequent exocytosis of the cortical granules induces separation of the vitelline layer from the egg plasma membrane. While these cortical changes are presumed to prevent the fusion of additional sperm, the subsequent late phase (between 1 and 4 min after fertilization) is characterized by reorganization of the egg cortex and microvilli (elongation) and by the metabolic shift to activate de novo protein and DNA syntheses. The latter biosynthetic events are crucial for embryonic development. Previous studies suggested that the early phase of fertilization was not a prerequisite for these changes in the second phase since the increase in the intracellular pH induced by the exposure of unfertilized sea urchin eggs to ammonia seawater could start metabolic egg activation in the absence of the cortical granule exocytosis. In the present study, we have demonstrated that the incubation of unfertilized eggs in ammonia seawater induced considerable elongations of microvilli (containing actin filaments) as a consequence of the intracellular pH increase, which increased the egg’s receptivity to sperm and made the eggs polyspermic at fertilization despite the elevation of the fertilization envelope (FE). These eggs also displayed compromised Ca2+ signals at fertilization, as the amplitude of the cortical flash was significantly reduced and the elevated intracellular Ca2+ level declined much faster. These results have also highlighted the importance of the increased internal pH in regulating Ca2+ signaling and the microvillar actin cytoskeleton during the late phase of the fertilization process.